A New Species of the Genus Trouessartia (Analgoidea, Trouessartiidae) from Ukraine - Burdejnaja, S.J.; Kivganov, D.A. (Вестник зоологии, 2011)
Trouessartia phylloscopi sp. n. from Willow Warbler Phylloscopus trochilus Linnaeus, 1758 (Passeriformes) (type locality: Zmeinij Island, Ukraine) is described. The new species is morphologically similar to T. microcaudata Mironov, 1983 from Barn Swallow Hirundo rustica Linnaeus, 1758.